MicroRNA-29a Promotes Pancreatic Cancer Growth by Inhibiting Tristetraprolin - Xian-Jun Sun; Bing-Yan Liu; Shuo Yan; Ting-Hui Jiang; Hui-Qin Cheng; Hao-Sheng Jiang; Yan Cao; Ai-Wu Mao (Cellular Physiology and Biochemistry, 2015)
Background/Aims: The microRNA (miR) 29 family has been studied extensively for its involvement in several diseases, and aberrant expression of its members is associated with tumorigenesis and cancer progression. Here, we examined the role of miR-29a in pancreatic cancer and the involvement of tristetraprolin (TTP). Methods: We monitored miR-29a and TTP expression in pancreatic cancer by qRT-PCR and western blotting. The effect of miR-29a on pancreatic cancer was determined through MTT assay and migration assay. The results were validated in the tumorigenesis model. Results: We found that miR-29a was up regulated in pancreatic tumor tissues and cell lines and positively correlated with metastasis. Ectopic expression of miR-29a increased the expression of pro-inflammatory factors and epithelial-mesenchymal transition (EMT) markers, through down regulating TTP. TTP was down regulated in tumor tissues, and its ectopic expression decreased cell viability and migration in vitro, inhibited tumor growth and the EMT phenotype in vivo, and reversed the effect of miR-29a on tumor cell proliferation and invasion in vitro and in vivo. Conclusion: Our results suggest that miR-29a acts as an oncogene by down regulating TTP and provide the basis for further studies exploring the potential of miR-29a and TTP as biomarkers and targets for the treatment of pancreatic cancer.